A Review on Carbon Dioxide Chemical Absorption for Biogas Upgrading (International Journal of Innovative Research in Computer Science & Technology, 2021)
The production, purification, as well as  improvement of biogas as a clean and renewable fuel  substitute has gotten a lot of attention. Biogas is produced  by anaerobic digestion and includes methane, carbon  dioxide, as well as trace amounts of many other gases.  Biogas purification removes trace gases from the biogas,  making it safe to use. Biogas upgrading produces  methane-rich biogas by removing excessive carbon  dioxide from the gas mixture. A number of carbon  dioxide extraction technologies may be utilized for biogas  upgrading. Chemical carbon dioxide absorption for  biogas upgrading, on either hand, is crucial since it  functions at or near ambient temperature as well  as pressure, reducing energy consumption. This article  discusses the chemical absorption of carbon dioxide via  amine scrubbing, caustic liquid scrubbing, and amino acid  saline water swabbing. Each of these biogas-upgrading methods is described. The study suggests that further  research is needed to optimize the use of chemical  absorption methods for biogas upgrading.
Keywords: Biogas; Chemical; CO2; CH4; Energy